Microstructurally-sensitive fatigue crack nucleation in Ni-based single and oligo crystals - Chen,B; Jiang,J; Dunne,F (Journal of the Mechanics and Physics of Solids, 2017)
An integrated experimental, characterisation and computational crystal plasticity study of cyclic plastic beam loading has been carried out for nickel single crystal (CMSX4) and oligocrystal (MAR002) alloys in order to assess quantitatively the mechanistic drivers for fatigue crack nucleation.The experimentally validated modelling provides knowledge of key microstructural quantities (accumulated slip, stress and GND density) at experimentally observed fatigue crack nucleation sites and it is shown that while each of these quantities is potentially important in crack nucleation, none of them in its own right is sufficient to be predictive. However, the local (elastic) stored energy density, measured over a length scale determined by the density of SSDs and GNDs, has been shown to predict crack nucleation sites in the single and oligocrystals tests. In addition, once primary nucleated cracks develop and are represented in the crystal model using XFEM, the stored energy correctly identifies where secondary fatigue cracks are observed to nucleate in experiments. This (Griffith-Stroh type) quantity also correctly differentiates and explains intergranular and transgranular fatigue crack nucleation.